PENERAPAN METODE SOCIAL STORY UNTUK MENINGKATKAN PEMAHAMAN PENDIDIKAN SEKSUAL PADA MASA PUBERTA SSISWA TUNAGRAHITA DI SLB C BUDI NURANI SUKABUMI - Putik Lestari, Diyanti; Yudha Pratama, Toni; Maslahah, Sayidatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the condition of mentally retarded students who experience puberty so they start to like the opposite sex, start touching the body parts of the opposite sex and make the person of the opposite sex they like feel uncomfortable until they decide to stop going to school. likes older people because they feel loved and are lured by money, are often invited to go to quiet places and are indicated to be receptive to sexual understanding. The aim of this research is to increase understanding of sexual education during puberty for mentally retarded students by applying the social story method. The research method used in this research is an experimental method with a single subject (single subject study) which is analyzed through data analysis within conditions and between conditions. The results of this study show a flat and increasing graph. This can be seen from the comparison of the mean level values ​​in each phase where the mean level in baseline phase 1 (A1) is 56%, while the mean level in the intervention phase (B) is 68,125%, and in the baseline phase 2 (A2) is 60%. So it can be said that the application of this social story method can increase understanding of sexual education during puberty for mentally retarded students.